Non-Alcoholic Fatty Liver Disease in Cardiac Patients with Overweight and Obesity - I. V. Logacheva; T. A. Ryazanova; V. R. Makarova; O. V. Surnina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. In this research, we set out to study organic changes in the heart and blood vessels of obese men suffering from non-alcoholic fatty liver disease (NAFLD) combined with cardiac pathology in the metabolically unhealthy phenotype (MUHP). Another objective consisted in establishing a relationship between liver damage and the pathology of the heart and blood vessels.Materials and methods. A group of 112 men (male)aged 61.2±1.7 diagnosed with the ischemic heart disease (IHD) and stage 1–3 arterial hypertension (AH) were examined during the stationary treatment in the Republican Clinical Diagnostic Centre (Izhevsk, Russia). The patients were divided into 3 groups according to their body mass index (BMI): 29 men with a BMI under 25 kg/m2(I group); 43 overweight men a BMI over 25 of kg/m2(II group); 40 men with obesity and a BMI above 30 of kg/m2(III group). Laboratory and non-invasive instrumental examinations required for the diagnostics of NAFLD and IHD were carried out, including liver ultrasound and FibroScan elastometry. Other examinations included the measurement of the intra-abdominal adipose tissue (IAT) and epicardial adipose tissue (EAT) thickness, the calculation of the visceral adiposity index (VAI), the estimation of endothelial dysfunction indicators, as well as the assessment of the structural and functional parameters of the heart and blood vessels.Results. In obese patients with pronounced NAFLD signs, IAT, EAT and VAI indicators are shown to increase in direct correlation with the parameters of liver steatosis. A relationship is established between the most significant structural and functional indicators of the heart (myocardial mass index, volume of the left atrium), blood vessels (endotheliumdependent vasodilation, the size of the intima-media complex of the common carotid artery) and NAFLD. It is demonstrated that the correlation coefficients grow with the progression of fatty infiltration and liver fibrosis signs.Conclusions. The results of the study have revealeda connection between the NAFLD presence and the main markers of visceral fat depots (IAT, EAT, VAI), which is shown to increase the risk of cardio-vascular complications in such patients. NAFLD is accompanied by endothelial dysfunction and a change in the most significant parameters of cardiac and vascular remodelling. These parameters manifest the progression of pathological changes in the liver parenchyma, which increases the cardio-metabolic risk in patients with MUHP.